Microwave-assisted synthesis of carbon nanodots from Bombax ceiba leaves for enhanced Tribo-corrosion resistance: An experimental and computational analysis - A. Mushira Banu; B. Arifa Farzana; N. MujafarKani; Abhinay Thakur; K. Riaz Ahamed; Ashish Kumar (Results in Surfaces and Interfaces)
This study presents a novel method for synthesizing carbon nanodots (BC-CNDs) from Bombax ceiba leaf extract via microwave assistance, yielding cost-effective, biodegradable, and water-soluble nanomaterials. Spectroscopic analysis, including FT-IR, UV–Vis, and fluorescence emission spectrophotometry, revealed the distinctive characteristics of BC-CNDs. Additionally, an anti-corrosive coating (BC-CNDs-C) was formulated by blending BC-CNDs with a plasticizer and binder. Quantitative evaluation of BC-CNDs-C showed an impressive inhibitory rate of 92.55% against corrosion. Electrochemical measurements indicated a notable increase in polarization resistance (Rp values: 1782.2 Ω cm2 for P1 to 4778.3 Ω cm2 for P4) and a decrease in corrosion current density (Icorr values: 0.065 μA/cm2 for P1 to 0.010 μA/cm2 for P4) with the incorporation of BC-CNDs, highlighting their effectiveness in enhancing corrosion resistance. Additionally, structural analyses via scanning electron microscopy (SEM) and atomic force microscopy (AFM) confirmed the reliability of BC-CNDs-C as a corrosion barrier. This research contributes to the development of sustainable materials for corrosion protection, addressing corrosion-related challenges in various industrial applications.